Aquiluna borgnonia gen. nov., sp. nov., a member of a Microbacteriaceae lineage of freshwater bacteria with small genome sizes. Issue 5 (17th May 2021) - Pitt, Alexandra; Schmidt, Johanna; Koll, Ulrike; Hahn, Martin W.
Abstract : The actinobacterial strain 15G-AUS-rot T was isolated from an artificial pond located near Salzburg, Austria. The strain showed 16S rRNA gene sequence similarities of 98.7 % to Candidatus Aquiluna rubra and of 96.6 and 96.7 % to the two validly described species of the genus Rhodoluna . Phylogenetic reconstructions based on 16S rRNA gene sequences and genome-based on amino acid sequences of 118 single copy genes referred strain 15G-AUS-rot T to the family Microbacteriaceae and therein to the so-called subcluster Luna-1. The genome-based phylogenetic tree showed that the new strain represents a putative new genus. Cultures of strain 15G-AUS-rot T were light red pigmented and comprised very small, rod-shaped cells. They metabolized a broad variety of substrates. Major fatty acids (>10 %) of cells were iso-C16 : 0, antiso-C15 : 0 and iso-C14 : 0 . The major respiratory quinone was MK-11 and a minor component was MK-10. The peptidoglycan structure belonged to an unusual B type. The closed genome sequence of the strain was very small (1.4 Mbp) and had a DNA G+C content of 54.8 mol%. An interesting feature was the presence of genes putatively encoding the complete light-driven proton pumping actinorhodopsin/retinal system, which were located at three different positions of the genome. Based on the characteristics of the strain, a new genus and a new species termed Aquiluna borgnonia is proposed for strain 15G-AUS-rot T (=DSM 107803 T =JCM 32974 T ).